2023
DOI: 10.1108/jhtt-01-2023-0015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of virtual reality and biological sex on the promotion of tourist destinations: effects on destination image, place attachment, and behavioural intention

Miguel Melo,
Guilherme Gonçalves,
Filipa Jorge
et al.

Abstract: Purpose This paper aims to generate knowledge of the impact of different virtual reality (VR) set-ups in tourism promotion regarding destination image, place attachment and behavioural intention. Design/methodology/approach The paper presents a comparative study of the impact of different visualisation technologies (video, immersive VR and multisensory immersive VR) to promote tourism destinations. The study’s dependent variables are destination image, place attachment and behaviour intention. Findings Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…Multisensory experiential tourism is favored by tourists nowadays, which leaves a long memory. Melo et al (2023) showed the positive impact of multisensory stimuli in promoting tourism destinations and enhancing the potential consumer's experience. This is surprising as tourism is inextricably linked to visuals.…”
Section: Multisensory Experiential Tourismmentioning
confidence: 99%
“…Multisensory experiential tourism is favored by tourists nowadays, which leaves a long memory. Melo et al (2023) showed the positive impact of multisensory stimuli in promoting tourism destinations and enhancing the potential consumer's experience. This is surprising as tourism is inextricably linked to visuals.…”
Section: Multisensory Experiential Tourismmentioning
confidence: 99%